Use of Copper Chloride in Thermoelectrochemical Cell for Solar Energy Conversion - C. Ameta, Suresh; Jain, J.L.; Jain, P.K.; Sharma, Deepali (Asian Journal of Chemistry, 2010)
A thermoelectrochemical cell containing copper chloride for solar energy conversion has been investigated. Effect of various parameters on the electrical output of the cell was also investigated. Current-voltage characteristics of the cell have been studied.